Profitability of litchi production in Dinajpur district of Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
This paper examined the profitability of litchi production in Dinajpur district of Bangladesh. Both primary and secondary data were used to accomplish the study. The primary data were collected during production period of litchi from February to May, 2015 through direct interviews with litchi growers. In total 60 litchi growers were interviewed from four villages of Dinajpur district to collect the necessary information. Profitability analysis was employed for analyzing the data and testing the hypotheses of the study. The life cycle of litchi is divided into five parts; juvenile or non-bearing stage, early bearing stage, young bearing orchards, full bearing orchards and old declining orchard, respectively. Per acre production in a season of its full bearing stage was considered for this paper. The production of litchi largely depends on its age and weather during the four month of litchi production. The major findings of the present study revealed that per acre net return of litchi considering selected varieties was Tk. 171624 based on one production period (February to May) in its full bearing stages which means litchi production is a profitable enterprise.J. Bangladesh Agril. Univ. 13(2): 283-289, December 2015